2018
DOI: 10.1021/acs.jpcc.8b09507
|View full text |Cite
|
Sign up to set email alerts
|

Does the Mg–I2 Battery Suffer Severe Shuttle Effect?

Abstract: Metallic anodes in Li/Na–X (X = S, Se, I2) batteries, in which the working mechanism is a conversion reaction, suffer severe corrosion and self-discharge caused by the shuttle effect. Beyond alkali metals, magnesium is also considered as the next-generation metallic anode for secondary batteries. The present study used atomic-scale modeling strategies to reveal the iodization reaction on the anode surface in the Mg–I2 battery. Under the low-coverage condition (Θ = 12.5%), the Mg(0001) surface can provide stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…For example, during the electrochemical process in the Li–I 2 system, the added NO 3 – could be reduced to NO 2 – accompanied by the formation of active oxygen ions, which would attack the 1,3-dioxolane (DOL) molecules in the electrolyte and induce their polymerization. , The polymerization of DOL, as well as the decomposition of TFSI- anions, led to the formation of solid electrolyte interphase (SEI) layer, which could further prohibit side reactions between lithium anode and iodine species . DFT simulation revealed similar effects of Mg­(NO 3 ) 2 additive in rechargeable Mg–I 2 batteries that the decomposed NO 2 molecules on the Mg metal substrate would prohibit the anode from iodine corrosion by forming a thin protecting layer composed of Mg–N–O …”
Section: Strategies To Build High-performance Ribsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, during the electrochemical process in the Li–I 2 system, the added NO 3 – could be reduced to NO 2 – accompanied by the formation of active oxygen ions, which would attack the 1,3-dioxolane (DOL) molecules in the electrolyte and induce their polymerization. , The polymerization of DOL, as well as the decomposition of TFSI- anions, led to the formation of solid electrolyte interphase (SEI) layer, which could further prohibit side reactions between lithium anode and iodine species . DFT simulation revealed similar effects of Mg­(NO 3 ) 2 additive in rechargeable Mg–I 2 batteries that the decomposed NO 2 molecules on the Mg metal substrate would prohibit the anode from iodine corrosion by forming a thin protecting layer composed of Mg–N–O …”
Section: Strategies To Build High-performance Ribsmentioning
confidence: 96%
“…103 DFT simulation revealed similar effects of Mg(NO 3 ) 2 additive in rechargeable Mg−I 2 batteries that the decomposed NO 2 molecules on the Mg metal substrate would prohibit the anode from iodine corrosion by forming a thin protecting layer composed of Mg−N−O. 104 Despite the fact that the nitrate-containing electrolytes helped restrain the shuttle effect of iodine species, recent research indicated that severe self-discharge behavior would still happen even using a Li anode precycled in a nitrate-containing electrolyte. 95 This result verified that the formed protective layer might not be the only reason for the enhanced electrochemical performance.…”
Section: Strategies To Build High-performance Ribsmentioning
confidence: 97%
“…18f). 249 However, in contrast to Li, when the iodine coverage is increased to 100%, the Mg surface exhibits good resistance to surface iodization without iodide exfoliation. 137 This indicates that the Mg anode could have good resistance to iodization-induced corrosion and self-discharge.…”
Section: Metal–iodine Batteriesmentioning
confidence: 99%
“…[21] It has already been confirmed that nitrates like LiNO 3 , NaNO 3, and Mg(NO 3 ) 2 additives performed critical roles in suppressing the shuttling effect and improving Coulombic efficiency. [51] Other additives, such as organic molecules, organic solvents, and nitrates, for improving the performance of Zn//I 2 batteries are worthy to be studied.…”
Section: Electrolyte Modulationmentioning
confidence: 99%